2021
DOI: 10.1051/e3sconf/202130901105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sugarcane Bagasse Fiber on Geopolymer Concrete when it is Subjected to Alternative Drying and Wetting

Abstract: Various types of fibers like glass, steel, coconut fiber, sugarcane bagasse fiber, etc are used to increase the mechanical properties of the concrete. SCBF is the final residue of the sugar industries which is used in this study. The objective of the paper is to study the effect of SCBF in geopolymer concrete (GPC) and conventional concrete (CC) of equivalent grade of M40 when it is subjected to alternative drying and wetting. The specimens are treated with water by alternative wetting and drying process. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Further, compressive strength loss due to exposure to continuous wetting and drying was 14.7% for fly ash-based GPC and 21.62% for OPC concrete [69]. Similarly, Srinivas et al [70] reported a 9.9% loss of compressive strength for GPC with fly ash and slag after exposure to 28 cycles. OPC under the same exposure conditions showed 10.89% reduction in compressive strength.…”
Section: Cyclic Wetting and Dryingmentioning
confidence: 86%
“…Further, compressive strength loss due to exposure to continuous wetting and drying was 14.7% for fly ash-based GPC and 21.62% for OPC concrete [69]. Similarly, Srinivas et al [70] reported a 9.9% loss of compressive strength for GPC with fly ash and slag after exposure to 28 cycles. OPC under the same exposure conditions showed 10.89% reduction in compressive strength.…”
Section: Cyclic Wetting and Dryingmentioning
confidence: 86%